2004
DOI: 10.1097/01.jom.0000126684.82825.0a
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical and Occupational Correlates of Work Productivity Loss Among Employed Patients With Depression

Abstract: Employers who are developing strategies to reduce health-related productivity loss may benefit from aiming their interventions at the employees who need them most. We determined whether depression's negative productivity impact varied with the type of work employees performed. Subjects (246 with depression and 143 controls) answered the Work Limitations Questionnaire and additional work questions. Occupational requirements were measured objectively. In multiple regression analyses, productivity was most influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(138 citation statements)
references
References 24 publications
8
122
0
8
Order By: Relevance
“…Two studies allowed estimation of the relative impact of absenteeism compared with presenteeism, yielding very different results. Stewart and associates found that 86% of total lost time associated with major depression was due to presenteeism (36), whereas Wang and associates found that only 25% was due to presenteeism (37 study also allowed additional investigation of the nature of the relation between presenteeism and depression symptoms, an area that has received very little investigation (38,39). Depression symptoms related to concentration and tiredness or sleep were each associated with impaired functioning in mental-interpersonal skills, time demands, and output.…”
Section: Descriptive Epidemiology: Work Disabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies allowed estimation of the relative impact of absenteeism compared with presenteeism, yielding very different results. Stewart and associates found that 86% of total lost time associated with major depression was due to presenteeism (36), whereas Wang and associates found that only 25% was due to presenteeism (37 study also allowed additional investigation of the nature of the relation between presenteeism and depression symptoms, an area that has received very little investigation (38,39). Depression symptoms related to concentration and tiredness or sleep were each associated with impaired functioning in mental-interpersonal skills, time demands, and output.…”
Section: Descriptive Epidemiology: Work Disabilitymentioning
confidence: 99%
“…We explored this further by reviewing epidemiologic studies that used more sophisticated measures of presenteeism in conjunction with a standardized measure of mental health. We located only 2 studies meeting the inclusion criteria (36,37), so we also included another study that met all the criteria except that it was in a selected population (38,39) (Table 3). Each study used a different measure of presenteeism.…”
Section: Descriptive Epidemiology: Work Disabilitymentioning
confidence: 99%
“…Psychological conditions are correlated with physical conditions (Lindberg et al 1994), with increased absenteeism among employees, and with increasing costs in the workplace (Johnson et al 1992;Stansfeld et al 1995). In particular, depression is emerging as a widespread problem insofar as it is related to a signiWcant portion of the costs associated with lost labor hours and lowered productivity (Berndt et al 2000;Kessler et al 2001;Lerner et al 2004;Simon et al 2000Simon et al , 2001. In addition, the job performance of workers with symptoms of depression inevitably declines in the absence of adequate treatment (Steward et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…efektywna decyzyjność, wzmożona koncentracja, konieczność opiniowania) oraz wymagają komunikacji i/lub częstych kontaktów z klientem [36].…”
Section: Psychospołeczna Charakterystyka Osób Ze Zdiagnozowaną Depresjąunclassified
“…Wyniki badań nie pozostawiają wątpliwości co do wpływu zaburzeń depresyjnych na obecność w pracy [34]. Absencja chorobowa wśród badanych osób z depresją wynosi 0,3-3,8 dnia pracy opuszczonego w miesiącu [34,36,37]. Badania, które wykazały powyżej 1 opuszczonego dnia, były badaniami klinicznymi obejmującymi cięższe przypadki chorobowe [34].…”
Section: Wpływ Choroby Na Produktywnośćunclassified